Percutaneous endoscopic treatment for osteoporotic vertebral compression fracture complicated with lumbar spinal stenosis: a case report and literature review - Liu, Mingzhi; Su, Kunpeng; Liu, Wentao; Ge, Hongtao; Xu, Derong; Zhou, Chuanli (Frontiers in Medicine, 2025)
BackgroundOsteoporotic vertebral compression fractures (OVCFs) and lumbar spinal stenosis are prevalent among the elderly population. The advent of minimally invasive surgical techniques has led to the emergence of percutaneous kyphoplasty (PKP), percutaneous endoscopic unilateral laminotomy and bilateral decompression (Endo-ULBD) as the prevailing treatment modalities for both conditions. However, elderly patients afflicted with a combination of both diseases frequently necessitate staged surgery or intricate surgical trauma with multiple incisions. Moreover, when a concomitant focal spinal deformity is present, conventional strategies frequently yield suboptimal outcomes.Case presentationThis case presented is that of a 70-year-old female patient with a medical history including hypertension, diabetes, and pacemaker implantation, who has recently developed progressive low back pain and radiating pain to the buttocks and lower extremities bilaterally. Radiological assessments revealed an L3 vertebral compression fracture with sclerotic margins, L2/3 disk-space collapse with a focal kyphotic deformity, and severe L2/3 spinal canal stenosis. A novel approach was employed in light of the patient’s fragile state and the risks associated with surgery, combining Endo-ULBD, PKP, and percutaneous cement discoplasty (PCD). This approach entailed the utilization of the intervertebral space channel as the sole access point and the percutaneous endoscopic incision as the solitary incision. The patient exhibited immediate postoperative pain relief and neurological improvement. Postoperative imaging confirmed resolution of the focal kyphotic deformity. On the second postoperative day, the patient could ambulate independently with lumbar support, and a 14-month follow-up period demonstrated continued clinical stability.ConclusionThis case demonstrates the feasibility of this surgical approach for older patients with OVCF and LSS. This approach offers a promising alternative to staged or open surgeries, with the potential to minimize operative trauma while ensuring symptom resolution and rapid recovery.